Enhancing exercisers` experience: a comprehensive review of insights from fitness instructors` behaviour and psychological impact - Braga-Pereira, R.; Furtado, G. E.; Campos, F.; Sampaio, A. R.; Teques, P. (International Journal of Sport and Exercise Psychology, 2026)
Fitness instructors seem to hold an important role as health promoters in fitness and health clubs, demanding an extensive comprehension of how to increase individuals` experiences and long-term adherence to exercise. The aims of the present systematic review were two-fold: (1) identify, analyse, and synthesise the evidence concerning fitness instructor`s behaviours perceived by exercisers, and (2) pinpoint potential research gaps to inform future research. Identification of studies entailed searches across the PubMed, Web of Science, Scopus, SPORTDiscus, and SciELO databases. The search strategy yielded 688 articles, with the analysis of titles and abstracts determining adherence to predefined criteria. Ultimately, 20 studies met the eligibility criteria. The review highlights the key role of exercisers` perceptions of fitness instructors` behaviours, meaningful in fostering elevated satisfaction with basic psychological needs, developing enjoyment, intrinsic motivation, and ultimately, bolstering the likelihood of sustained exercise engagement. The findings stress important considerations about interpersonal behaviours, in particular need-supportive and need-thwarting behaviours, pertaining to exercisers` psychological and behavioural outcomes. Furthermore, consistent with the secondary purpose of this study, some research gaps that need further investigation were identified (e.g., longitudinal research, integrated study of psychological and physiological variables, digital fitness). The novelty of this systematic review lies in furnishing a structured insights repository capable of steering the interventions of fitness instructors, and to provide a foundation for future research uncovering potential research gaps.